A field study of adaptive thermal comfort in primary and secondary school classrooms during winter season in Northwest China. (15th May 2020) - Jiang, Jing; Wang, Dengjia; Liu, Yanfeng; Di, Yuhui; Liu, Jiaping
Abstract: Current thermal comfort evaluation models are based on the average level of an entire society, which is difficult to use as a direct guide for the design of classroom thermal environments in primary and secondary schools. Research was made on a group of pupils during winter in rural areas in Northwest China to analyze their thermal comfort level and regulation of their thermal adaptability under controlled and uncontrolled environments. Using questionnaire surveys and field measurements, 781 sets of valid data in controlled conditions and 345 sets in uncontrolled conditions were collected. Along with the measured air temperature, relative humidity, air velocity, globe temperature, and clothing level, a significant difference was observed between the thermal sensation vote and predicted mean vote. The preferred temperature and comfortable temperature range were obtained by analyzing the actual percentage of dissatisfied pupils and their thermal expectations. The result subsequently indicated that the comfortable temperature ranges for 90% of the pupils was 13.0–18.0 °C. The upper limit of comfortable temperature was 3.0 °C lower than the lower limit of the current recommended international standard in winter, and the clothing insulation was approximately 0.5 clo higher than the recommended value. By considering the influence of outdoor climate on the behavioral habits, psychological expectations, and physiological regulation, an adaptive thermal comfort model for primary and secondary school students in cold environments is proposed. The findings can serve as a guideline for the design and evaluation of heating systems in primary and secondary schools in rural areas. Highlights: Thermal responses to classroom thermal environments were surveyed in winter. The pupils' comfortable temperature range was approximately 13.0–18.0 °C in winter. Pupil who experienced a warmer environment had greater psychological expectations. Neither the PMV m nor the current adaptive model can be applied in this study. Adaptive thermal comfort model is proposed for pupils' thermal sensation evaluation.